Pediatric melioidosis: Call for better awareness and early diagnosis! - Tina Damodar; Meena Dias; Neethu Kishor; Hilda Pinto (Wolters Kluwer Medknow Publications, 2015)
Pediatric melioidosis is an under-diagnosed entity and rarely reported from India. This condition, if not treated early and appropriately, can have a fatal outcome. A 17-month-old female child presented with fever and ulcer on the right leg; she eventually succumbed to the infection. Culture from blood and wound swab from ulcer site grew Burkholderia pseudomallei.